CULTURAL ADAPTATION OF CHINESE STUDENTS AS THE NEED OF THEIR EDUCATION ABROAD PROCESS - Zhao, Xin; Ding, Shaojie; Kalashnyk, Lyubov; Luhova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to a sharp problem of educational practice: ways of cultural adaptation of foreign (in particular, Chinese) students in new host society as a condition of their successful education abroad. Chinese students now form the largest abroad students` community in main countries of the world. As the Chinese way of living and the education traditions differ a lot from the countries` they usually would like to continue their education at, cultural adaptation is seen in the article as the need for a comfortable education process both for the students came and the University host them. The Main methods of Chinese students` cultural adaptation process are under consideration of the research, paying attention to the period (stage) a student finds himself / herself at that also can be seen as the aim of the research. As to the methods, the ones traditionally used in social studies and general research work were used: ethnographic descriptions and census data, scientific method to collect empirical evidence, method of analysis, etc. As the result was presented a set of methods that can be used by a host University on condition of the Chinese students` cooperation to level down the cultural shock period for the student and to speed up his/her entering the host culture society.